Axial load-axial deformation behaviour of circular concrete columns reinforced with GFRP bars and helices. (1st June 2016) - Karim, Hogr; Sheikh, M. Neaz; Hadi, Muhammad N.S.
Highlights: Investigate behaviour of concrete columns reinforced with GFRP bars and GFRP helices. Model for load-deformation of concrete columns reinforced with GFRP bars and helices. Helix pitch effect on the behaviour of columns reinforced with GFRP bars and helices. Abstract: Fibre Reinforced Polymer (FRP) bars has attracted a significant amount of research attention in the last three decades to overcome the problems associated with the corrosion of steel reinforcing bars in reinforced concrete members. A limited number of studies, however, have investigated the behaviour of concrete columns reinforced with FRP bars. Also, available design standards either ignore the contribution of or do not recommend the use of GFRP bars in compression members. This study reports the results of experimental investigations of concrete specimens reinforced with GFRP bars and GFRP helices as longitudinal and transverse reinforcement, respectively. A total of five circular concrete columns of 205 mm in diameter and 800 mm in height were cast and tested under axial compression. The experimental results showed that reducing the spacing of the GFRP helices or confining the specimens with CFRP sheet led to improvements in the strength and ductility of the specimens. Also, an analytical model has been developed for the axial load-axial deformation behaviour of the circular concrete columns reinforced with GFRP bars and helices. The model has been validated with the experimental results.